Ligninolytic characteristics of Pleurotus ostreatus cultivated in cotton stalk media - Li, Guoqing; Wang, Yahui; Yu, Deshui; Zhu, Peilei; Zhao, Guiyun; Liu, Caiyu; Zhao, Hongyuan (Frontiers in Microbiology, 2022)
Biodelignification is widely regarded as a low-efficiency process because it is usually slow and difficult to control. To improve its efficiency and understand its mechanism, the present study analyzed the delignification characteristics of Pleurotus ostreatus grown on a cotton stalk medium. The results demonstrated that all strains of P. ostreatus can selectively degrade the cotton stalk lignin. When cultured in a cotton stalk medium for 60 days, P. ostreatus degraded lignin primarily during its mycelium growth and produced laccase and manganese peroxidase with high activity levels (two peaks for each enzyme), but no detectable lignin peroxidase. The results of 1H-NMR and FTIR analyses of significant changes in lignin structure revealed that syringyl (S) lignin units were more degraded than guaiacyl (G) lignin units, with a significantly elevated G/S ratio. The GC–MS analysis of low-molecular-weight compounds revealed that the delignification resulted in the formation of alcohols, organic acids, benzodiazepines, and alkanes. Identified benzodiazepines implied the degradation of G and S units of lignin. These findings will help to improve the efficiency of biodelignification and expand our understanding of its mechanism.